2017
DOI: 10.1016/j.vetmic.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of antimicrobial resistant Escherichia coli in dogs: Prevalence, associated risk factors and molecular characteristics

Abstract: Resistance to antimicrobials, in particular that mediated by extended spectrum β-lactamases (ESBL) and AmpC β-lactamases are frequently reported in bacteria causing canine disease as well as in commensal bacteria, which could be a potential health risk for humans they come into contact with. This cross-sectional study aimed to estimate the prevalence and investigate the molecular characteristics of ESBL and plasmid encoded AmpC (pAmpC)-producing E. coli in the mainland UK vet-visiting canine population and, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
75
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 42 publications
14
75
3
Order By: Relevance
“…In two cross‐sectional studies of dogs in the UK, associations with raw feeding were found for AmpC phenotype E. coli (Schmidt et al ) and for third‐generation cephalosporin‐resistant E. coli (Groat et al ). Another UK cross‐sectional study reported a strong association between feeding raw poultry and faecal ESBL E. coli among veterinary‐visiting dogs (Wedley et al ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…In two cross‐sectional studies of dogs in the UK, associations with raw feeding were found for AmpC phenotype E. coli (Schmidt et al ) and for third‐generation cephalosporin‐resistant E. coli (Groat et al ). Another UK cross‐sectional study reported a strong association between feeding raw poultry and faecal ESBL E. coli among veterinary‐visiting dogs (Wedley et al ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
“…In two cross-sectional studies of dogs in the UK, associations with raw feeding were found for AmpC phenotype E. coli and for third-generation cephalosporin-resistant E. coli (Groat et al 2016). Another UK cross-sectional study reported a strong association between feeding raw poultry and faecal ESBL E. coli among veterinary-visiting dogs (Wedley et al 2017). In addition to ESBL/AmpC resistance studies, raw feeding has also been identified as a risk factor for faecal shedding by dogs of E. coli exhibiting other antimicrobial drug resistances (Leonard et al 2015, Groat et al 2016.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Three out of 325 dogs were found to carry ESBL-EC (0.9%; 95% confident interval 0.3-2.7% using Wilson Score interval) ( Table 1). The prevalence of ESBL-E in Swedish dogs was lower than that reported from other European countries [2][3][4][5], but more in-depth comparisons are difficult to make because of general application of different methodologies. However, a Dutch study conducted in 2014-2016 used similar methods as the current study and they found that 10.6% of the 555 dogs carried ESBL-E [4].…”
Section: Resultsmentioning
confidence: 66%
“…In Copenhagen, Denmark, 1.9% of dogs' faecal deposits in public gardens were positive for ESBL-producing Escherichia coli (ESBL-EC) and in Paris, France, 18.5% of dogs carried ESBL-EC, while 81.8% of dogs carried ESBL-EC in Faisalabad, Pakistan [1][2][3]. Other nationwide studies reported ESBL/pAmpC-E carriage rates of 9.0% in United Kingdom and 22.2% in Turkey, while in the Netherlands, 10.6% of dogs were reported to carry ESBL-E [4][5][6]. Occurrence of MRCPS in dogs generally appears to be lower with reports around 0-3% positive dogs [7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%